Pelaksanaan Pembelajaran Seni Budaya Secara Online Di Kelas VII SMP Negeri 31 Padang - Irvandy Satria; Esy Maestro (SENDRATASIK UNP, 2021)
This study aims to reveal themelodicainstructionusing online learning system in grade VII of SMP Negeri 31 Padang.The stages include planning, implementation, and evaluation in the COVID-19 pandemic situation. The theory used to observethe activity is learning and instruction theory. The research used qualitative method with a descriptive analytic approach. The data were collected through observation, interviews, and literature study. The data analysis was carried out through identification, classification, clarification, analysis, explanation, and conclusion. The results show that the learning of Culture and Arts at SMP Negeri 31 Padang is still carried out but it is conducted online at home.Related to these learning situations and conditions, the teachers designlearning which is relatively different from face-to-face learning in class. The planning that the teachers dois preparing learning materials and send them to students via WA. It contains messages, subject matter, activities carried out, and obligations which must be fulfilled by students. The learning implementation includes controlling students’ learning by asking students to send a video of blowing, fingering, and practicing the song Ibu Kita Kartini which is sent in the form of a video recording. Almost all students do the video recordings and sent them on time. However,a small number of studentsdo not send the video recordings on time. This is the evaluation and barriers to learning melodica online. The learning outcomes ofgrade VII students at SMP Negeri 31 Padang are good. The obstacles faced by the teachers include the presentation, practice, and learning outcomeswhich are very inadequate.